Experimental study on controlling factors reducing hydrogen concentration in a simulated fuel debris storage container using passive autocatalytic recombiner - Gaku TAKASE; Kazuyuki TAKASE (Journal of Thermal Science and Technology)
In the decommissioning work of Tokyo Electric Power Company Holdings Fukushima Daiichi nuclear power plant, the water contained in the fuel debris is radiolyzed when the fuel debris containing water is taken out from the bottom of the reactor vessel and packed into a storage container, and as a result, hydrogen and oxygen will generate in the storage container. Since hydrogen is flammable gas, it has a high risk of combustion and explosion. In order to reduce the hydrogen concentration and to secure long-term integrity of the storage container for fuel debris, Passive Autocatalytic Recombiner (PAR) was used. It consists of a spherical alumina as a base material and a small amount of platinum coated on the outer surface, and a prototype of PAR was fabricated and installed into an experimental container. The experimental container roughly simulated the volume of a currently designed fuel debris long-term storage container. In order to clarify the controlling factors affecting the reduction of hydrogen concentration in the storage vessel including PAR and the magnitude of the effect due to those, parameter experiments were carried out for each of the supposed controlling factors. As controlling factors, the hydrogen flow rate, the quantity of PAR, the installation position of PAR, the water-repellent treated PAR, the porosity in a container and so on were taken into consideration, and their effects on the reduction of hydrogen concentration were quantitatively evaluated. As a result, the conditions of each controlling were clarified to reduce the hydrogen concentration in the experimental container with PAR to less than 4 wt%, which is the lower explosion limit of hydrogen.